2010
DOI: 10.1111/j.1600-0528.2009.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between use of asthma drugs and prevalence of demarcated opacities in permanent first molars in 6‐to‐8‐year‐old Danish children

Abstract: Children with prescriptions for inhaled asthma drugs before the age of 3 years did not have an overall increased risk of demarcated opacities in first permanent molar but they seemed to have an increased risk of the severe demarcated opacities, i.e. opacities resulting in macroscopic loss of tooth substance, and possibly a need for restorative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 18 publications
2
29
1
6
Order By: Relevance
“…Pacientes pediátricos com asma grave, de início precoce, têm um risco aumentado de defeitos do esmalte dentário 18 . Quando esse ponto é levado em consideração, os defeitos mais encontrados são as opacidades difusas e demarcadas 19 . Crianças com histórias de infecções respiratórias ou catapora, expostas à fumaça de cigarro, com infecções do trato urinário e otite estão predispostas a hipoplasia do esmalte 30 .…”
Section: História De Doenças Na Infânciaunclassified
See 2 more Smart Citations
“…Pacientes pediátricos com asma grave, de início precoce, têm um risco aumentado de defeitos do esmalte dentário 18 . Quando esse ponto é levado em consideração, os defeitos mais encontrados são as opacidades difusas e demarcadas 19 . Crianças com histórias de infecções respiratórias ou catapora, expostas à fumaça de cigarro, com infecções do trato urinário e otite estão predispostas a hipoplasia do esmalte 30 .…”
Section: História De Doenças Na Infânciaunclassified
“…A ocorrência de problemas pré-natais e neonatais pode aumentar o risco de presença de defeitos de esmalte em crianças 2,[5][6][7][8] . Na dentição permanente, traumas na dentição decídua são associados à presença de defeitos de esmalte [9][10][11] , assim como à experiência de cárie na dentição decídua [12][13][14][15][16] e à ocorrência de doenças sistêmicas na infância [17][18][19] . A presença de defeitos hipoplásicos tem relação com predisposição à cárie 16,20 e à sensibilidade den-tária, maloclusão e problemas estéticos, que podem promover problemas de ordem social e psicológica, interferindo na qualidade de vida das crianças 21 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…While it's opposite to the results obtained by other studies who found that there is a significant association between dental defects and evidence for anemia (33,34) For Bronchial asthma cases with enamel defects showed statistically significantly higher prevalence than cases with no enamel defects, this was assured by the findings reported by other studies (32,35,36). This can be hypothesized that pediatric asthma patients with dental enamel defects have probably experienced previous episodes of oxygen deprivation and ameloblasts are highly sensitive to oxygen supply (32) , also asthma drugs (either inhaled or oral) have been suspected to increase the prevalence of enamel defects (37).…”
Section: (30)mentioning
confidence: 99%
“…Por outro lado, vários autores não associam problemas perinatais com a MIH. (58,62,85). Semelhante com achados do presente estudo, onde apenas 11;11% (N=1) das crianças com MIH foi prematuro, dado sem significado estatístico.…”
Section: Etapa 3 -Análise De Prontuário Médicounclassified